Quantification De L’erosion Hydrique En Utilisant Le Modèle Rusle Et Déposition Intégrée Dans Un Sig. Cas Du Bassin Versant De L’oued Isly (Maroc Oriental) - El Hafid Driss; Akdim Brahim (European Scientific Journal, ESJ, 2018)
In Morocco, hydric erosion is the main factor in soil degradation. It is a dynamic and very complex phenomenon, linked to natural and anthropic factors that are difficult to control in time and space. Land degradation has visible impacts on the environment and hinders economic and social development. The consequences of erosion, both upstream and downstream of watersheds, are costly for the Moroccan economy. The Oued Isly watershed is an elongated mountan basin with an area of 1312km2. It is part of eastern Morocco. It is located in the south of Oujda city. Wadi Isly is characterized by irregular flow. Its flow increases during the winter and early spring. Extreme flows are recorded after exceptional and very intense rain in the Touissit and Guenfouda mountains. The watershed of Wadi Isly knows currently a very active erosive dynamic that affects all the slopes on both banks of the Oued Isly. Several factors contribute to the processes of soil degradation, such as climatic aggression and anthropogenic action. The objective of this study is to estimate soil losses at the Wadi Isly watershed by the application of the universal soil loss equation (USLE) and the use of GIS and Remote sensing. This study also aims to discuss the amplifying factors of the erosive phenomenon in this semi-arid environment.